2018
DOI: 10.1002/ange.201808291
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral Functionalized Cage as a Tool to Create Frustrated Lewis Pairs

Abstract: Afrustrated Lewis pair (FLP) system was obtained by confinement of the Lewis base partner,aVerkadess uperbase,i nam olecular cavity.W hereas the model superbase lacking cavity displayed no catalytic activity in Morita-Baylis-Hillman (MBH) reactions,w hen associated to titanium (IV) chloride,t he encaged superbase turns out to be an efficient catalyst under the same conditions.T he crucial role of the endohedral functionalized cage on catalytic performance was further demonstrated by the fact that model superba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Spectral data is consistent with literature values. 46 1 H NMR (400 MHz, CDCl 3 ) δ 7.24 (d, J = 8.1 Hz, 2H), 7.15 (d, J = 7.9 Hz, 2H), 6.74 (t, J = 4.2 Hz, 1H), 5.52 (s, 1H), 3.36 (br s, 1H), 2.48 – 2.42 (m, 2H), 2.42 – 2.35 (m, 2H), 2.34 (s, 3H), 2.04 – 1.95 (m, 2H). 13 C NMR (126 MHz, CDCl 3 ) δ 200.6, 147.4, 141.3, 138.8, 137.3, 129.2, 126.5, 72.6, 38.8, 25.9, 22.7, 21.3.…”
Section: Methodsmentioning
confidence: 99%
“…Spectral data is consistent with literature values. 46 1 H NMR (400 MHz, CDCl 3 ) δ 7.24 (d, J = 8.1 Hz, 2H), 7.15 (d, J = 7.9 Hz, 2H), 6.74 (t, J = 4.2 Hz, 1H), 5.52 (s, 1H), 3.36 (br s, 1H), 2.48 – 2.42 (m, 2H), 2.42 – 2.35 (m, 2H), 2.34 (s, 3H), 2.04 – 1.95 (m, 2H). 13 C NMR (126 MHz, CDCl 3 ) δ 200.6, 147.4, 141.3, 138.8, 137.3, 129.2, 126.5, 72.6, 38.8, 25.9, 22.7, 21.3.…”
Section: Methodsmentioning
confidence: 99%
“…This report is the first example of an encaged superbase as organocatalyst. In a later study, 24 has been shown to form a frustrated Lewis‐pair (FLP) with TiCl 4 [50] . The FLP is able to catalyze the Morita‐Baylis‐Hilman (MBH) reaction between p ‐chlorobenzaldehyde and cyclopentenone (Figure 10, right).…”
Section: Endohedral Group Is Functional By Itselfmentioning
confidence: 96%
“…Then, the encaged Verkade's superbase P @ 2 a was combined with a Lewis acid, titanium (IV) chloride, in order to create a Frustrated Lewis Pair (FLP) system . It was demonstrated that the acid‐base reaction between these two partners was prevented by the confinement of the proazaphosphatrane in a cage structure.…”
Section: Proazaphosphatranes (Verkade's Superbases) In Confined Spacesmentioning
confidence: 99%
“…Then, the encaged Verkade's superbase P@2 a was combined with a Lewis acid, titanium (IV) chloride, in order to create a Frustrated Lewis Pair (FLP) system. [21] It was demonstrated that the acid-base reaction between these two partners was prevented by the confinement of the proazaphosphatrane in a cage structure. Indeed, when the model P@3 a is mixed with TiCl 4 the chlorinated azaphosphatrane PCl + @3 a is formed while this process does not occur when the confined superbase is used as Lewis base (Scheme 5 (b)).…”
Section: Catalytic Activity In Confined Spacesmentioning
confidence: 99%